Evaluation of the Direct Effect of Bilateral Deep Brain Stimulation of the Subthalamic Nucleus on Levodopa-Induced On-Dyskinesia in Parkinson's Disease - Li, Jiping; Mei, Shanshan; Jia, Xiaofei; Zhang, Yuqing (Frontiers in Neurology, 2021)
Objective: This study aims to evaluate the direct anti-dyskinesia effect of deep brain stimulation (DBS) of subthalamic nucleus (STN) on levodopa-induced on-dyskinesia in Parkinson's disease (PD) patients during the early period after surgery without reducing the levodopa dosage. Methods: We retrospectively reviewed PD patients who underwent STN-DBS from January 2017 to October 2019 and enrolled patients with levodopa-induced on-dyskinesia before surgery and without a history of thalamotomy or pallidotomy. Unified Dyskinesia Rating Scale (UDysRS) parts (I+III+IV) and the Unified Parkinson’s Disease Rating Scale part III (UPDRS-III) were monitored prior to surgery and at the 3 months follow-up, the location of active contacts was calculated by postoperative CT-MRI image fusion to identify stimulation sites with good anti-dyskinesia effect. Results: There were 41 patients enrolled. The postoperative levodopa equivalent daily dose (LEED) (823.1±201.5 mg/day) was not significantly changed from the baseline (844.6±266.1 mg/day, P = 0.348), while the UDysRS On-Dyskinesia subscores significantly decreased from 24 [10–58] to 0 [0–18] (median [range]) after STN stimulation (p<0.0001). The levodopa-induced on-dyskinesia recurred in stimulation-off/medication-on state in all the 41 patients and disappeared in 39 patients when the DBS stimulation was switched on at 3 months follow-up. The active contacts which correspond to good effect for dyskinesia were located above STN, and the mean coordinate was 13.05±1.24mm lateral, -0.13±1.16mm posterior, and 0.72±0.78 mm superior to the midcommissural point. Conclusions: High-frequency electrical stimulation of the area above the STN can directly suppress levodopa-induced on-dyskinesia.